2021
DOI: 10.3390/jcm10051129
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Muscle Health in Predicting the Risk of Asymptomatic Vertebral Fracture in Older Adults

Abstract: Background: The utility of muscle health for predicting asymptomatic vertebral fracture (VF) is uncertain. We aimed to determine the effects of muscle health on bone quantity and quality in the older adults and to integrate these factors into a predictive model for VF. Methods: We prospectively recruited participants with a body mass index <37 kg/m2. The total lean mass (TLM), appendicular skeletal muscle index, presence of sarcopenia, and bone mineral density were determined by dual-energy X-ray absorptiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…There are several reports about the risk factors of asymptomatic VFs. However, only a few studies have examined the association between asymptomatic VF and muscle mass, muscle strength, fat mass, and spinal alignment [27,28]. The current study showed that asymptomatic VFs were associated with BMI, BF%, knee pain VAS score, KOA, and painDETECT score in the univariate analysis.…”
Section: Discussionsupporting
confidence: 45%
“…There are several reports about the risk factors of asymptomatic VFs. However, only a few studies have examined the association between asymptomatic VF and muscle mass, muscle strength, fat mass, and spinal alignment [27,28]. The current study showed that asymptomatic VFs were associated with BMI, BF%, knee pain VAS score, KOA, and painDETECT score in the univariate analysis.…”
Section: Discussionsupporting
confidence: 45%
“…Population studies have shown that the annual incidence of VCFs is 10.7 per 1000 women and 5.7 per 1000 men[ 38 ]. Dr. Lin surveyed the VCF in another study with 600 patients, which enrolled 186 men and 404 women[ 39 ]. The ratio of men and women was similar to that in our study, including each treatment subgroup.…”
Section: Discussionmentioning
confidence: 99%